Evolution of woody life form on tropical mountains in the tribe Spermacoceae (Rubiaceae). Issue 3 (8th March 2017) - Neupane, Suman; Lewis, Paul O.; Dessein, Steven; Shanks, Hunter; Paudyal, Sushil; Lens, Frederic
Abstract : PREMISE OF THE STUDY: Spermacoceae are mainly an herbaceous group in the Rubiaceae. However, a few lineages are woody and are found in a diverse range of habitat types. Three of the largest woody lineages ( Arcytophyllum, Hedyotis, and Kadua ) are characterized by their distribution in the moist tropical mountains and have disjunct distribution patterns with respect to their closest relatives. In this study, we explore the cases of derived woodiness in these three lineages and their diversification dynamics in the tropical mountains of Asia, the Pacific, and the Americas. METHODS: By combining phylogenetic results with wood anatomical studies, we estimated timing of origin of the three woody groups, inferred their ancestral traits and ancestral distribution ranges, analyzed their associations with the tropical upland habitat, and elucidated their diversification across tropical mountains. KEY RESULTS: The three woody clades originated and diversified from herbaceous ancestors in close association with the tropical upland habitat during the Miocene. The ancestral range for Asian‐Pacific Hedyotis is Africa/Madagascar and continental Asia for Pacific Kadua . The complex geological history of tropical Asia allowed Hedyotis to diversify faster and create narrow endemics near oceans in the highlands of the Western Ghats in India, Sri Lanka, Southeast Asia including southeastern China, and New Guinea. CONCLUSIONS: The three major woody clades in Spermacoceae have gained their woodiness independently from one another, subsequent to colonization by their ancestors from a different geographic environment. The evolution and diversification along the tropical mountain orogeny is strongly linked with the formation of woody habit and many narrow endemic species.